A new cave Sinella species from South China (Collembola: Entomobryidae) - Zhang, Feng; Deharveng, Louis (Zootaxa, 2009)
Sinella whitteni sp. nov., a new cave species from South China is described. It is characterized by inner differentiated tibiotarsal chaetae ciliated, 2 inner small basal ungual teeth, serrate outer edge of the unguiculus, short smooth distal part of dens, presence of m1i and p4 on Th. II and 5 + 5 macrochaetae on central Abd. IV. The complete s-chaetotaxy is reported in the genus Sinella for the first time. It is most close to another cave species S. trogla Chen & Christiansen, 1993, from which it differs in short mucronal spine, presence of m1i, m2i2, p4 and absence of m4i on Th. II, absence of unpaired tooth on unguis, and absence of large finely ciliated chaetae on manubrium.